Early childhood caries status and its associated factors among young children in a rural area of Cambodia. Issue 1 (April 2020) - Kubota, Yu; San Pech, Nhep; Durward, Callum; Ogawa, Hiroshi
Abstract: Background: The purpose of this cross-sectional study was to measure prevalence and severity of early childhood caries (ECC), and its associated factors among 1- and 2-year-old children in Kampong Cham province, Cambodia. Materials and methods: Data, from a representative sample of 128 children (69 males, 59 females; mean age = 22.98 ± 7.68 months), were collected at seven villages in Khpob Ta Nguon district, Kampong Cham province from May to October in 2018. The dental caries status was recorded following WHO guidelines. The socio-economic status, dietary habits and oral hygiene habits of the children were assessed through an interview questionnaire administered to their primary caregivers. Results: ECC prevalence was 50.0%. The mean dft was 2.46 ± 3.08, and 100% of cavitated lesions were untreated. A logistic regression revealed that 1-year-old children who continued night breast-feeding after 12 months were more likely to have ECC (OR = 5.32, 95%CI = 1.33–21.30), whereas the 2-year-old children who continued night breast-feeding beyond 12 months (OR = 13.36, 95%CI = 2.14–82.31), bottle-feeding after 12 months (OR = 6.10, 95%CI = 1.56–23.87), and children who did not adopt tooth brushing by the 1st birthday (OR = 32.23, 95%CI = 4.51–230.54) were more likely to have ECC. Conclusion: The findings of this study indicate that ECC prevalence and severity among this group of rural Cambodian children were high. Oral health programs focusing ECC prevention from an early age should be conducted in this population.